Recognition Memory in Psychotic Patients - H. Ellis; K. De Pauw; G. N. Christodoulou; J.-P. Luaute; E. Bidault; K. Szulecka (Behavioural Neurology)
Preliminary data are reported from experiments in which Warrington's (1984) Recognition Memory Tests were given to patients with misidentification delusions including the Capgras type and to psychotic patients. The results showed a profound impairment on face recognition for most groups, especially those with the Capgras delusion. It was rare to find a patent whose score on the word test was anything but normal.